2018
DOI: 10.4236/ojoph.2018.83020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes with a New Model of Extended Depth of Focus Intraocular Lens

Abstract: Purpose: To evaluate the early clinical outcomes of a new diffractive extended depth-of-focus (EDOF) intraocular lens (IOL). Methods: Prospective case series enrolling patients undergoing cataract surgery with implantation of the EDOF IOL AT LARA (Carl Zeiss Meditec, Jena, Germany). Distance, intermediate and near visual acuity were evaluated during a follow-up of 1 month. Likewise, defocus curve, binocular mesopic contrast sensitivity, perception of photic phenomena, patient satisfaction and spectacle indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…To mitigate these visual disturbances coupled with the ever-increasing demand for better intermediate vision, extended-depth-of-focus (EDOF) IOLs have been introduced. EDOF lens technology provides continuous range of focus [ 1 , 9 14 ], leading to fewer unwanted visual disturbances (i.e., photic phenomena, glare, halos) without sacrificing other visual outcomes [ 10 , 11 , 15 ]. Numerous studies to date have shown EDOF IOLs produce similar results in both uncorrected far and intermediate vision as trifocal IOLs [ 1 , 5 , 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate these visual disturbances coupled with the ever-increasing demand for better intermediate vision, extended-depth-of-focus (EDOF) IOLs have been introduced. EDOF lens technology provides continuous range of focus [ 1 , 9 14 ], leading to fewer unwanted visual disturbances (i.e., photic phenomena, glare, halos) without sacrificing other visual outcomes [ 10 , 11 , 15 ]. Numerous studies to date have shown EDOF IOLs produce similar results in both uncorrected far and intermediate vision as trifocal IOLs [ 1 , 5 , 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%